Financing for development : an OPEC presence : statements (OPEC Fund for International Development ViennaAT, 2002)
Presents the statements of OPEC [Fund] member countries at the conference. Adumbrates a determination and resolve to continue to work for global peace, progress and security, by staying involved, staying engaged and ensuring that those who today consider themselves marginalised and left out of the main stream do have a future to look toward.
Keywords: ECONOMIC AND SOCIAL DEVELOPMENT